Analisis Faktor-Faktor Yang Mempengaruhi Impor Gula di Indonesia Tahun 1992-2022 - Anggraeni, Nimas Rizki Tri; Mubarokah, Mubarokah; Widayanti, Sri (Universitas Respati Indonesia, 2024)
This research aims to determine the development of sugar imports in Indonesia and to analyze the influence of sugar production, sugar consumption, domestic sugar prices, international sugar prices, and the rupiah exchange rate on sugar imports in Indonesia in 1992-2022. This research is quantitative research and uses time series data. The data sources used were obtained from the Central Statistics Agency, Ministry of Agriculture, Ministry of Trade and several related studies. The analysis model used is development trend analysis and ECM (Error Correction Model). The results of research (1) in trend analysis in 1992-2022 obtained the equation Y = 2,317,827.5 + 174,230x showing that the average development of the volume of sugar imports was 2,317,827.5 tons and each year there was an average increase in sugar imports amounting to 174,230 tons. (2) Results of Multiple Linear Regression analysis of the ECM Model in the long term and short term. The variables that show a significant positive effect on sugar imports are domestic sugar prices and international sugar prices, while other variables such as sugar production, sugar consumption and the rupiah exchange rate show a positive effect. insignificant to sugar imports in 1992-2022.